Application of microcomputers in chemical engineering teaching - Sukhendu B. Bhowmik (1986)
As the latest contribution of information technology, microcomputer-based instruction, nowadays, is being increasingly and extensively used in undergraduate chemical engineering teaching. This thesis teaches microcomputers in the tutorial classroom where a microcomputer is regarded as a sophisticated calculator and in the laboratory where it acts like a conventional controller. After defining the types of computers and the three main programming languages (Basic, Fortran and Pascal), the thesis provides a general description of microcomputers followed by a formal discussion of computers in education where the ways of computer teaching in two universities are described. Five types of teaching programs have been distinguished. These are: (1) Simple problem solving program (2) Design calculation program (J) Simulation program (4) Flowsheeting program, and (5) Control program. Twenty four teaching programs of different categories have been developed and are described in detail. In addition, two simple interfaces based on two simulation programs (SIMBA and HEDP) have also been developed for the first year teaching laboratory at Loughborough. Finally, it should be noted that the intention is that this thesis will be of value in the teaching of chemical engineering sciences.